Executive Information System for the Prevention and Handling of Sexual Violence in School Environments - Nst, Nur Falah Akbar; Fauzi, Muhammad (Jurnal ICT : Information and Communication Technologies, 2025)
Sexual violence in schools is a serious issue that can negatively impact the mental and physical well-being of students. The lack of an integrated system for reporting and monitoring cases often results in suboptimal prevention and response efforts. This study aims to design and implement an executive information system that assists school management, especially decision-makers, in making data-driven decisions regarding the prevention and handling of sexual violence. The system development follows the waterfall method, consisting of requirements analysis, system design, implementation, and testing phases. The result of this research is a web-based system with an interactive dashboard that displays case reports, incident trends, and follow-up recommendations. The system was tested using usability testing and the results indicated that the system is user-friendly and effectively supports the decision-making process. The implementation of this executive information system is expected to enhance responsiveness, transparency, and effectiveness in addressing sexual violence within the school environment.